BUCOVINA TOURISM IN THE AGE OF DIGITIZATION - Cioban, Gabriela-Liliana (Revista de turism - studii și cercetări în turism, 2024)
Tourism in the age of digitalisation or Tourism 4.0 is an important element for the competitiveness, growth and sustainability of tourism enterprises. Digitisation and technological development helps tourism enterprises to be competitive in the global market. Therefore, the topic provides an analysis of the concept of tourism 4.0 and digital technologies such as artificial intelligence, virtual reality, augmented reality, big data, Internet of Things, blockchain, mobile technologies, cloud computing, robotics and social media in tourism. The insights analysed bring to the fore the ability of digitisation to add value to tourism products and experiences, provide many new opportunities for business and contribute to customer satisfaction and sustainable tourism development. This highlights the potential of Tourism 4.0 to make a decisive contribution to the sustainable development of tourism. Tourism 4.0 technologies offer many facilities as well as those that contribute to personalising the customer experience, obtaining information on traveller preferences and behaviour; flexibility in booking and cancellation policies and not least tourists use technology and mobile applications to search for up-to-date information.